(untitled) (Indian Journal of Public Health Research & Development, 2020)
Human Immunodeficiency Virus (HIV) results in a weakened immune system, making it vulnerable to various types of infections, systemic disorders and weight loss. In Indonesia, the incidence and mortality rates from HIV/AIDS were still relatively high, especially in Makassar, South Sulawesi Province. This study aimed to determine the dominant factors associated with nutritional status on people living with HIV/AIDS (PLWHA). This research was a quantitative research with cross-sectional design, involving 80 respondents of PLWHA aged ? 18 years. Data collection used a structured questionnaire included demographic, clinical, and behavioral factors, while nutritional status was measured by body mass index (BMI). The results showed that most of respondents had normal nutritional status (67.5%), followed by underweight (20%) and overweight (12.5%). Gastrointestinal symptoms were the dominant factor related to nutritional status (BMI) after controlling confounding variables such as smoking habits, food security status, and alcohol consumption (AOR = 4.78 and p-value = 0.01). Nutrition education could improve the nutrition intake and dietary behaviour of PLWHA at Kelompok Dukungan Sebaya foundation (YPKDS) in Makassar City.